Characteristics of adult out‐of‐hospital cardiac arrest in the National Emergency Medical Services Information System. Issue 4 (4th June 2020) - Chan, Hei Kit; Okubo, Masashi; Callaway, Clifton W.; Mann, N. Clay; Wang, Henry E.
Abstract: Background: The national incidence and characteristics of out‐of‐hospital cardiac arrest in the United States is unclear. We sought to describe the national characteristics of adult out‐of‐hospital cardiac arrest reported in the National Emergency Medical Services Information System (NEMSIS). Methods: We used 2016 NEMSIS data, consisting of most emergency medical services (EMS) responses from 46 states and territories. We limited the analysis to adult (age ≥18 years) emergency "9‐1‐1" events. We defined out‐of‐hospital cardiac arrest as: (1) patient condition reported as cardiac arrest, (2) EMS reported attempted resuscitation of cardiac arrest, (3) EMS performance of cardiopulmonary resuscitation (CPR), or (4) EMS performance of defibrillation. We determined the incidence of adult out‐of‐hospital cardiac arrest among EMS responses. We also determined patient demographics (age, sex, race, ethnicity, location, US census region, and urbanicity), response characteristics (dispatch complaint and elapsed time) and clinical interventions (medications and procedures) of adult out‐of‐hospital cardiac arrest. We analyzed the data using descriptive techniques, calculating binomial proportions with exact 95% confidence intervals (CI). Results: Among 18, 679, 873 adult 9‐1‐1 responses, there were 224, 992 with patient condition cardiac arrest, 344, 274 with EMS‐reported attempted cardiac arrest resuscitation, 149, 775 with EMS performance of CPR, and 185, 388 cases with EMS performance of defibrillation, resulting in a total of 574, 824 out‐of‐hospital cardiac arrest (incidence 30.8 per 1000 EMS 9‐1‐1 responses, 95% CI = 30.69–30.85). Among identified out‐of‐hospital cardiac arrest responses, most involved patients who were older (mean = 62.4 ± 20.1 years). Most out‐of‐hospital cardiac arrest occurred at home (58.8%), in the South census region (65.4%), and in urban settings (79.8%). The most commonly reported medications used in out‐of‐hospital cardiac arrest were: epinephrine (22.5%), amiodarone (2.9%), sodium bicarbonate (6.2%), glucose (3.0%), and naloxone (5.1%). Commonly reported procedures included CPR (26.1%), orotracheal intubation (14.2%), bag‐valve‐mask ventilation (10.1%), manual defibrillation (29.3%) and automated external defibrillation (5.6%). Out‐of‐hospital cardiac arrest EMS treatment times were: elapsed response time (median = 7 minutes [interquartile range (IQR) = 5–10]), scene time (median = 17 minutes [IQR = 12–25]), and elapsed transport time (median = 11 minutes [IQR = 6–17]). Conclusions: Using information available in the 2016 NEMSIS data, we estimate that there were over 570, 000 reported adult out‐of‐hospital cardiac arrests in the United States. These results highlight the challenges of characterizing the epidemiology of adult out‐of‐hospital cardiac arrest in the United States.